Tunable Potassium Ion Conductivity and Magnetism in Substituted Layered Ferrates. Issue 4 (10th December 2020) - Albrecht, Ralf; Hunger, Jens; Hoelzel, Markus; Suard, Emmanuelle; Schnelle, Walter; Doert, Thomas; Ruck, Michael
Abstract: Five substituted oxohydroxoferrates K2–x (Fe, M )4 O7–y (OH)y ( M =Si, Ge, Ti, Mn, Ir) were synthesized in a potassium hydroxide hydroflux with a molar base‐water ratio q (K) of about 0.9. While the hexagonal prisms of K2–x (Fe, Ti)4 O7–y (OH)y crystallize in P 63 / mcm, all other compounds form hexagonal plates with the trigonal space group P 3 ‾ 1 m . The crystal structure of the oxohydroxoferrates resembles ß ‐alumina. It consists of honeycomb layers ∞ 2 Fe2 O6 ] of edge‐sharing [FeO6 ] octahedra, where the hexagonal voids are capped by vertex‐sharing [FeO4 ] tetrahedra pairs. The cavities between the oxoferrate layers host the potassium ions. Depending on M, the substitution affects different iron positions and varies between 5 and 20 %. The magnetic structures of the antiferromagnetic compounds were determined by neutron powder diffraction. The potassium ion conductivity was characterized by electrochemical impedance spectroscopy at room temperature. By storing the oxohydroxoferrates in air or annealing them at 700 °C the ion conductivity was significantly increased, e. g. to 5.0 ⋅ 10 −3 S cm −1 for a pressed pellet of the iridium substituted compound. Abstract : The substituted oxohydroxoferrate K2–x (Fe, M )4 O7–y (OH)y ( M =Si, Ge, Ti, Mn, Ir) were obtained from hydroflux. All compounds are strong antiferromagnets. The pillared crystal structures facilitate potassium ion conductivity up to 5 ⋅ 10 −3 S cm −1 at room temperature. Substitution, heat treatment, and chemical leaching are parameters that influence the potassium content and the cation mobility.